(untitled) (International Journal of Health, Animal Science and Food Safety, 2017)
Mycoplasma gallisepticum (MG) is a highly economical and persistent threat of poultry industry in Bangladesh. Indirect ELISA (iELISA) and Serum plate agglutination test (SPA) is available serological test for diagnosis of MG antibodies. The aim of this research was conducted on the basis of comparison on diagnosis results between iELISA and SPA test for MG antibody in same sample in layer chicken. Total 563 serum samples were collected and tested for MG antibody by both iELISA and SPA test. Out of 563 samples 363 (64.48%) samples were positive by iELISA and 316 (56.13%) samples were positive in SPA test. The higher incidence of MG antibody was found in chicken at 50-56 weeks and flock size was 3000-4200 as 69.63% by iELISA and 61.21% by SPA and in Sonali breeds 69.08% by iELISA and 60.64% by SPA. The results showed the comparatively higher number of positive results in iELISA test than SPA test. So the findings of the study demonstrated that a significant (p<0.05) difference between iELISA and SPA test present. The study may helpful for screening the flock for MG and small-holding farmers may use SPA test rather than iELISA test due to rapid, easy and cost effective.